MISOGYNY & SEXISM TOWARDS WORKING-CLASS WOMAN IN SOPHIE TREADWELL’S MACHINAL - Saputra, I Gusti Ngurah Alexander Surya Bayu; Leony, Jessica (UC Journal: ELT, Linguistics and Literature Journal, 2023)
This research aims to analyze misogynist behavior towards women such as hatred, prejudice, sexism, and violence which can also be called misogyny. Many people have read, watched, or listen to movies, books, podcasts, etc. about feminism but many of them are sometimes still not aware or did not notice how women can be a victim of misogyny regardless of how small the actions are. These actions or behavior still lingers even in this modern day, the researcher will compile, analyze, and clarify those actions and why it is considered misogyny. This paper wishes to give the purpose of making people understand and aware of those actions or behaviors and also aims at those who do not understand the attitude, behavior, and actions of misogyny, either for those who do it intentionally or unintentionally.